Tumor Reduction in Primary and Metastatic Pancreatic Cancer Lesions With nab-Paclitaxel and Gemcitabine: An Exploratory Analysis From a Phase 3 Study. Issue 2 (February 2017) - Kunzmann, Volker; Ramanathan, Ramesh K.; Goldstein, David; Liu, Helen; Ferrara, Stefano; Lu, Brian; Renschler, Markus F.; Von Hoff, Daniel D.
Abstract : Objectives: Results from the phase 3 Metastatic Pancreatic Adenocarcinoma Clinical Trial (MPACT) led to approval of nab -paclitaxel plus gemcitabine for first-line treatment of metastatic pancreatic cancer. The current analysis evaluated the effects of nab -paclitaxel plus gemcitabine versus gemcitabine on primary pancreatic and metastatic lesions. Methods: In this analysis of the previously described MPACT trial, changes in pancreatic and metastatic tumor burden were assessed using independently measured diameters of lesions on computed tomography or magnetic resonance imaging scans. Changes in the sums of longest tumor diameters were summarized using descriptive statistics and were included in a multivariate analysis of overall survival. Results: Primary pancreatic lesion measurement was feasible. Reductions in primary pancreatic tumor burden and metastatic burden from baseline to nadir were significantly greater with nab -paclitaxel plus gemcitabine versus gemcitabine. Baseline pancreatic tumor burden was independently predictive of survival. Both regimens elicited linear reductions in primary pancreatic and metastatic tumor burden through time. There was a high within-patient concordance of tumor changes between primary pancreatic lesions and metastatic lesions. Conclusions: This analysis of MPACT demonstrated significant tumor shrinkage benefit for nab -paclitaxel plus gemcitabine in both primary pancreatic and metastatic lesions, supporting ongoing evaluation of this regimen in locally advanced disease.